KAJIAN KEPUASAN MAHASISWA TERHADAP LAYANAN PROSES PEMBELAJARAN JARAK JAUH PADA PROGRAM STUDI D2 PERPUSTAKAAN - Rahardjo, Djoko; Suharmini, Sri; Majidah, Majidah (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
Universitas terbuka is one of university in Indonesia that implement a remote and open learning system. Learning distance requirements are not carried out by using media, both print (module) and non-print (audio/video, computer/internet, radio broadcasting, and television). To serve students spread throughout Indonesia, excellent service is required. UT continues to increase its commitment to promoting academic quality and one of the academic qualities that need to be improved is the learning process where in the learning process there are general service aspects, aspects of registration services, tutorial service aspects, either TTM tutorials or online tutorials (TUTON), practicum services, services teaching materials, Online Bookstore services (TBO), SIPAS services and aspects of service for administering examinations. This study is intended to determine the level of satisfaction of students, especially D2 Library students of FISIP-UT Library, to the services provided by UT. The method used is quantitative and qualitative methods. The results of the assessment of satisfaction and importance are ≥ 50% of students are satisfied and feel an interest in the various services provided by UT.